SOLVE THE FOLLOWING.
@MODERATOR CAN GIVE ANSWER IN MESSANGES BOX.
@WRONG ANSWER WILL REPORTED.
@SOLVE IN NUMBER WISE EX. SUCH AS QUES NO.10Q (d).
![](https://hi-static.z-dn.net/files/d02/04502e64e091b242c5c7b245e2b4231a.jpeg)
![](https://hi-static.z-dn.net/files/db3/8c0bf4ecdc4b932129692376f3f25140.jpeg)
Answers
Step-by-step explanation:
9(a):-
18ab(16a^2-9b^2)÷(9ab(4a+3b)
=>(2×9ab)[(4a)^2-(3b)^2]÷(9ab(4a+3b))
=>(2×9ab)(4a+3b)(4a-3b)÷(9ab(4a+3b))
=>9ab(4a+3b)[2+4a-3b]÷(9ab(4a+3b))
=>9ab(4a+3b)[2+4a-3b]/(9ab(4a+3b))
=>4a-3b+2
18ab(16a^2-9b^2)÷(9ab(4a+3b) = 4a-3b+2
_________________________________
9(b):-
(p^2-5p+6)÷(p-2)
=>(p^2-2p-3p+6)/(p-2)
=>[p(p-2)-3(p-2)]/(p-2)
=>(p-2)(p-3)/(p-2)
=>p-3)
(p^2-5p+6)÷(p-2) = (p-3)
_________________________________
10(a):-
7a^2b^2+b^2 simplifies to 7a^2b^2 is wrong
addition is wrong
=>7a^2b^2+b^2
=>b^2(7a^2+1)
__________________________________
10(b):-
7x/(7x+8) is simplifies to 1/8
Division is wrong
7x/(7x+8)
__________________________________
10(c):-
(4p-7q)(4p+7q) simplifies to 16p^2+49q^2 is wrong
(4p-7q)(4p+7q)
this is in the form of (a+b)(a-b).
Where, a= 4p
b=7q
we know that
(a+b)(a-b) = a^2-b^2
(4p-7q)(4p+7q)
=>(4p)^2-(7q)^2
=>16p^2-49q^2
(4p-7q)(4p+7q) = 16p^2-49q^2
____________________________________
10(d):-
65x^3/65x^3 simplifies to 0
This Division is wrong
=>65x^3/65x^3
=>1
65x^3/65x^3 = 1
___________________________________
11.
Given equation is x^2+ax-2 = (x-1)(x+b)
=>x^2+ax-2 = x^2+bx-x-b
=>x^2+ax-2 = x^2+(b-1)x-b
On comparing both sides then
b=2 and
=>a=b-1
=>a=2-1
=>a =1
The value of a = 1 and b=2
__________________________________
12.
Given pilynomial is a^2-24a+114
We know that by factor theorem
If P(x) is a polynomial and (x-a) is a factor then P(a)=0
Now a-12 = 0=>a=12
Now P(a)=a^2-24a+114
=>P(12)=(12)^2-24(12)+114
=>144-288+114
=>258-288
=>-30
So, (a-12) is not a factor of a^2-24a+114
___________________________________
13.
Given that
Area of a square = (4a^2+6a+6a+9) sq.units
Area of a square = side×side
=>Side×Side = 4a^2+6a+6a+9
=> Side×Side= 2a(2a+3)+3(2a+3)
=>Side ×Side = (2a+3)(2a+3)
Length of the side of the square = (2a+3) units
____________________________________
Answer:
ooye bro meine kuch nhi kiya mere bhi ques delete huye hain yeh tune kiye the kya